Income Inequality in Rich Countries During the 1980s - Timothy Michael Smeeding; John F. Coder (Luxembourg Income Study (LIS), 1993)
Using two period comparisons of six wealthy nations, the authors look at the extent of inequality at three levels of income: earned income, market income, and after tax and transfer disposable income. Interesting implications of the results are discussed.
Keywords: 330; Einkommensverteilung; Australien; Großbritannien; Kanada; Niederlande; Schweden; USA